Challenges of IT freelancers on digital labor platforms: A topic model approach - Lisa Gussek; Alex Grabbe; Manuel Wiesche (Electronic Markets, 2023)
Freelancers working on digital labor platforms have to deal with many challenges. IT freelancers should be considered separately due to special characteristics such as high skill level or collaborative nature of IT work. Through a Latent Dirichlet Allocation analysis of 2804 forum posts with over 20,000 comments from IT freelancers and additional qualitative analysis, we assign themes to each identified topic, cluster them into aggregated dimensions, and illustrate the interrelationships in a model of IT freelancing. Thus, we examine the challenges of IT freelancers and synthesize them. We extend the challenges of online freelancing already outlined in the literature and identify four IT-specific challenges for IT freelancers. Therefore, we improve our understanding of how IT work is performed on digital labor platforms and which particular aspects should be considered in future research. Furthermore, we highlight implications for practitioners, i.e., IT freelancers on the one hand and platform owners on the other hand.
Keywords: F66; J4; 620; IT work; IT freelancing; Digital labor platforms; Challenges; Gig economy